2004
DOI: 10.1007/s00122-003-1567-7
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of adult plant resistance to stripe rust in the wheat cultivar Kariega

Abstract: The wheat cultivar Kariega expresses complete adult plant resistance to stripe rust in South Africa. The aim of this investigation was to determine the extent and nature of variability in stripe rust resistance in a population of 150 doubled haploid lines generated from a cross between Kariega and the susceptible cultivar Avocet S. Analysis of field data for adult plant stripe rust resistance identified two major QTLs and two minor QTLs in the resistant cultivar Kariega. The two major QTLs were located on chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 33 publications
8
60
0
2
Order By: Relevance
“…This result confirms that our controlled greenhouse environment mimicked well the field conditions. The good correlation observed here between greenhouse and field phenotypes is important since there are contrasting reports about the reproducibility of field evaluation results under greenhouse conditions (Ramburan et al 2004). …”
Section: Effect Of Yr36 Is Temperature Dependentsupporting
confidence: 53%
“…This result confirms that our controlled greenhouse environment mimicked well the field conditions. The good correlation observed here between greenhouse and field phenotypes is important since there are contrasting reports about the reproducibility of field evaluation results under greenhouse conditions (Ramburan et al 2004). …”
Section: Effect Of Yr36 Is Temperature Dependentsupporting
confidence: 53%
“…Vazquez et al [43] identified multiple APR QTL in Stephens with one identified on 4A by linkage to SSR marker Xbarc70; Eltan did not share that allele [31]. The 4A QTL from IDO444, described by Chen et al [42], was found at a similar location to a QTL in Kariega [41]. These two varieties and Avocet S share a common allele at Xgwm160.…”
Section: Varietymentioning
confidence: 99%
“…Wheat farmers were confronted with new disease management decisions, fungicide application costs and yield losses, susceptible cultivars had to be withdrawn and large breeding populations were discarded due to susceptibility (Pretorius et al, 2007a). Reports on pathogenic variation (Boshoff & Pretorius, 1999;Boshoff et al, 2002a), chemical control (Boshoff et al, 2003), sources of resistance (Boshoff et al, 2002b;Ramburan et al, 2004;Prins et al, 2005) and screening techniques (Pretorius et al, 2007b) laid the foundation for managing this disease. Through careful breeding, selection and screening many South African wheat cultivars are currently considered resistant or moderately resistant to stripe rust.…”
Section: Disease Controlmentioning
confidence: 99%